Optimization of the training plan based on the assessment of the functional state of the athletes - Khaydarov Ulugbek Rustamovich; Muzaffarova Sabrina Mirshod Qizi (Proximus Journal Publishing, 2024)
in the stage of Evolution Development, Morpho–functional characteristics of the human body are formed gradually in a consistent way, while in sports where intensive physical exercise is required to be carried out continuously, these heavy loads and their qualitative and quantitative indicators change rapidly. Such rapid change can lead to functional disorders in the human body and cause the origin of various diseases. For this reason, the fixation on heavy physical loads and the identification of functional changes that occur in the body under its influence requires, first of all, the improvement of the adaptation process of the athlete's body, the level of tension and fatigue, the reevaluation of indicators of speed, endurance, working capacity and the perfection of recovery measures.
Keywords: level of physical capabilities; correlation communication; parameters; fat mass